The Learning Activity of Teacher in Teacher's WorkingGroup (A Site Study on KKG at Pucang Harapan GroupSub Mranggen Demak) - Santoso, Edy (2011)
The objectives of this research are to describe (1) the characteristics of the teacher's individual learning activity on KKG at Pucang Harapan Group, Mranggen Demak (2) the teacher's group learning activity on KKG at Pucang Harapan Group, Mranggen Demak. This is qualitative research. That is conducted on KKG at Pucang Harapan Group, Mranggen Demak. Main subject in this research are leader, member, and manager of KKG. The data collection method in this research are in-depth interview, observation, and documentation. While data analysis is done by establishing data collection, data reduction, data display, and drawing conclusion or verification. the data validity test are using credibility, transferability, conformability and dependability. The research result shows that (1) the individual activity of teacher on KKG at Pucang Harapan Group, Mranggen Demak is very active. The activities are conducted by giving idea or things, doing identification, doing problem analyzes or problem solving, through workshop or sharing idea and also implemented some program that are made by KKG manager such as learning model, learning method, media and means of learning. (2) Teacher activity of learning group is doing active activity in KKG. The learning activity of teacher group is doe by made a group based on the class and the lesson teacher. The teacher is doing discussion and simulation such as learning method of lesson study, class action research, and cooperative learning. Beside that teacher simulation is executed by doing socialization activity that is done by the entire KKG member but in different location according to the determined class.